Evaluating the West Virginia Interpretive Guide Heritage Steward Program. Issue 2 (November 2015) - Arbogast, Doug; Smaldone, Dave; Balcarczyk, Kelly
West Virginia University's Extension Service partnered with the Recreation, Parks, and Tourism Resources Program to offer an entry level certification opportunity to interpretive guides in West Virginia. The result of this partnership is the West Virginia Interpretive Guide Heritage Steward Program aimed at providing low-cost, widely available training course to guides throughout the state. The course is divided into two components—a set of online modules and an in-person skill assessment workshop. This exploratory study used a retrospective post-then-pre survey design to assess the course impact on participants' beliefs related to the effectiveness of the course, as well as self-reported changes in interpretive competency. Results indicated the course was successful in increasing participant competence related to developing and delivering interpretive talks. This effective regionally based certification course is potentially a model that could be used to expand personal interpretive certification opportunities for guides.